Implementasi Pembelajaran Daring pada Mata Kuliah Statistik Berbasis Video - Nusrotus Saidah (Universitas Islam Malang, 2021)
This study aims to describe the student response and effectiveness of online learning for statistics courses in the Tarbiyah and teacher science faculty, Unisnu Jepara. The sample of this study were students from the faculty of Tarbiyah and teacher training at Unisnu Jepara in the Islamic religious education study program, English language education and primary school teacher education who took statistical courses, as many as 107 students. The research instrument was a questionnaire about student perceptions of video-based online learning distributed via google form. The data analysis technique in this study used descriptive statistics to reveal several indicators of student perceptual responses to online learning in statistics courses. The results of the analysis show that the implementation of online learning using video is 3.77 (good) material aspects, compatibility aspects 3.59 (good), complexity 3.38 (sufficient), triability aspects 3.51 (good) and usefulness aspects 3, 6 (good). With this video-based learning an effort to provide material in the form of video tutorials practicing data analysis with Spss in statistics courses.